A Review and Thermal Analysis of a Heat Exchanger with Conical Cross Flow Arrangement - Koirala, Lila Raj (KEC Journal of Science and Engineering, 2026)
The frequently used device for transfer of heat energy is the heat exchanger which allows the heat transfer from one fluid to another. The heat exchanger with cross flow arrangement has tube-side and outside fluid flows perpendicular to each other. It often occurs that in the cross-flow arrangements due to perturbations of fluid flow and heat transfer conditions, some parts of tubes in bundle are excluded from an intensive heat transfer process. This results in the effects as if the tubes were progressively shorter in comparison to their real length and the thermally active tube bundle were conical in shape (trapezium). The thermal analysis of the cross-flow arrangement for any number of tubes in bundle with progressive changes (decrease / increase) in tube length has been carried out and presented in this paper. To solve this problem the method of the "weighted mean value of outside fluid temperature" was applied. The numerical results are presented in diagrams with the effectiveness of tube side fluid versus the effectiveness of the outside fluid. The outside liquid flows one time in direction with narrowing cross-section that results in increasing of its velocity, and the second time it flows in opposite direction where the stream expands and liquid slows down its velocity. It was found that for assumed equal number of transfer units (NTU) of a heat exchanger for these both cases the second one leads to higher values of effectiveness.